2012
DOI: 10.1111/j.1365-2621.2011.02926.x
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase from jumbo squid (Dosidicus gigas) muscle: purification and partial characterization

Abstract: Lysyl oxidase (LOX; E.C.1.4.3.13) was purified from jumbo squid muscle (Dosidicus gigas) with 1900-fold and yield 1.9%, and characterized for the first time. The purification procedure consisted of fractionation with urea and a combination of size-exclusion and anion-exchange chromatography. The enzyme had a molecular weight of 32 kDa, as estimated by SDS-PAGE. Using a specific LOX substrate (1,5-diaminopentane), its optimum activity was determined at pH 8.2 and 65°C. Activation energy (E a ) of the enzyme was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…It was possible to obtain a crude extract of Lox from the three organisms (Table ), with a higher extraction yield in CT from octopus ( p > .05); however, these values were lower than those seen in jumbo squid (Torres‐Arreola et al, ), in which a total Lox yield of 6.74% protein was obtained from its arms. These findings might be associated with the crosslinking degree of the collagen fibers since a higher content of the enzyme leads to a greater formation of covalent bonds involving Pyr (Torres‐Arreola et al, ). Based on the SDS‐PAGE electrophoretic profile of those crude extracts (Figure ), it is suggested that the molecular mass of Lox extracts obtained from octopus, guitarfish and cazon could be around 30–34 kDa.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…It was possible to obtain a crude extract of Lox from the three organisms (Table ), with a higher extraction yield in CT from octopus ( p > .05); however, these values were lower than those seen in jumbo squid (Torres‐Arreola et al, ), in which a total Lox yield of 6.74% protein was obtained from its arms. These findings might be associated with the crosslinking degree of the collagen fibers since a higher content of the enzyme leads to a greater formation of covalent bonds involving Pyr (Torres‐Arreola et al, ). Based on the SDS‐PAGE electrophoretic profile of those crude extracts (Figure ), it is suggested that the molecular mass of Lox extracts obtained from octopus, guitarfish and cazon could be around 30–34 kDa.…”
Section: Resultsmentioning
confidence: 91%
“…Regarding Lox activity, the highest total activity was detected in the octopus crude extract ( p < .05), with no differences between guitarfish and cazon ( p ≥ .05) (Table ), while the specific activity presented the opposite behavior, with octopus having the lowest values ( p < .05). All the evaluated species showed lower specific activity than those described for jumbo squid ( D. gigas ), of 4.1 × 10 –3 nm H 2 O 2 /mg protein in the mantle (Ramírez‐Guerra, Fimbres‐Romero, et al, ) and 4.23 nM H 2 O 2 /mg protein in the arms (Torres‐Arreola et al, ). These differences in activity can be attributed to the differences that tend to exist between marine species, size, habitat, or catch season (Morales et al, ), which affects the arrangement of the crosslinking of collagen fibers (Torres‐Arreola et al, ) and the high concentration of Pyr (Ramírez‐Guerra, Fimbres‐Romero, et al, ).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations